The role of axial dispersion in fixed beds of reacting solid particles - Akosman, C; Walters, JK (Elsevier Science Sa, 2004)
Axial dispersion or back mixing appears to be responsible for adverse mass velocity effects (or low conversion) observed in laboratory fixed beds of reacting solid particles. One method by which axial dispersion effects can be eliminated from such fixed beds is the use of solid diluents. The reaction of hydrogen chloride gas with calcined limestone particles was carried out in a laboratory fixed bed in order to study the axial dispersion effects in fixed beds of reacting particles. The calcined limestone particles were diluted with inert mullite beads to give varying bed lengths. Experiments were conducted with an inlet HCl gas concentration of 0.5 mol.% in N-2 at 565 degreesC. The dispersion equations for the fixed bed of reacting solid particles were used to interpret the experimental results. It has been shown that lengthening the fixed bed with solid diluent increases solid conversion (decreases effluent gas concentration). (C) 2003 Elsevier B.V. All rights reserved.
Keywords: axial dispersion; solid dilution; HCl removal; hot gases; solid utilisation